IMF Survey, Volume 30, Issue 13. (IMF Survey; IMF Survey, 2001)
Following are edited remarks by Stanley Fischer, the IMF's First Deputy Managing Director, at the Argentine Bankers Association Meeting in Buenos Aires on June 25. The full text of his speaking notes is available on the IMF's website at www.imf.org.